Fused filament printing of specialized biomedical devices: a state-of-the art review of technological feasibilities with PEEK. Issue 3 (8th February 2021) - Rezvani Ghomi, Erfan; Eshkalak, Saeideh Kholghi; Singh, Sunpreet; Chinnappan, Amutha; Ramakrishna, Seeram; Narayan, Roger
Abstract : Purpose: The potential implications of the three-dimensional printing (3DP) technology are growing enormously in the various health-care sectors, including surgical planning, manufacturing of patient-specific implants and developing anatomical models. Although a wide range of thermoplastic polymers are available as 3DP feedstock, yet obtaining biocompatible and structurally integrated biomedical devices is still challenging owing to various technical issues. Design/methodology/approach: Polyether ether ketone (PEEK) is an organic and biocompatible compound material that is recently being used to fabricate complex design geometries and patient-specific implants through 3DP. However, the thermal and rheological features of PEEK make it difficult to process through the 3DP technologies, for instance, fused filament fabrication. The present review paper presents a state-of-the-art literature review of the 3DP of PEEK for potential biomedical applications. In particular, a special emphasis has been given on the existing technical hurdles and possible technological and processing solutions for improving the printability of PEEK. Findings: The reviewed literature highlighted that there exist numerous scientific and technical means which can be adopted for improving the quality features of the 3D-printed PEEK-based biomedical structures. The discussed technological innovations will help the 3DP system to enhance the layer adhesion strength, structural stability, as well as enable the printing of high-performance thermoplastics. Originality/value: The content of the present manuscript will motivate young scholars and senior scientists to work in exploring high-performance thermoplastics for 3DP applications.